Myocardial Metabolism in Heart Failure with Preserved Ejection Fraction - Henry, JA; Couch, LS; Rider, OJ (MDPI, 2024)
Heart failure with preserved ejection fraction (HFpEF) is increasingly prevalent and now accounts for half of all heart failure cases. This rise is largely attributed to growing rates of obesity, hypertension, and diabetes. Despite its prevalence, the pathophysiological mechanisms of HFpEF are not fully understood. The heart, being the most energy-demanding organ, appears to have a compromised bioenergetic capacity in heart failure, affecting all phenotypes and aetiologies. While metabolic disturbances in heart failure with reduced ejection fraction (HFrEF) have been extensively studied, similar insights into HFpEF are limited. This review collates evidence from both animal and human studies, highlighting metabolic dysregulations associated with HFpEF and its risk factors, such as obesity, hypertension, and diabetes. We discuss how changes in substrate utilisation, oxidative phosphorylation, and energy transport contribute to HFpEF. By delving into these pathological shifts in myocardial energy production, we aim to reveal novel therapeutic opportunities. Potential strategies include modulating energy substrates, improving metabolic efficiency, and enhancing critical metabolic pathways. Understanding these aspects could be key to developing more effective treatments for HFpEF.